2022
DOI: 10.3390/su14138048
|View full text |Cite
|
Sign up to set email alerts
|

Field Measurement of Central CO2 Heat Pump Water Heater for Multifamily Retrofit

Abstract: Domestic hot water heating of multifamily buildings accounts for a substantial portion of the energy load of existing buildings. This load is made up of both the energy required to produce hot water and the energy needed to maintain the temperature of the heated water within a building’s distribution piping so that heat can be promptly delivered to building occupants as needed. Properly designed heat pump water heater (HPWH) systems have the ability to improve efficiency in both water heating and temperature c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…However, their research specifically focused on reducing energy consumption for cooling purposes. Banks et al [28] reported the results of their research on heat-pump water-heating systems. Of interest is the research conducted by Zhang et al [29], which compares the primary energy consumption, environmental impact, and heating costs of coal-fired and wall-fired gas boiler heating systems, direct electric heating systems, and air-source heat pump systems using a life cycle analysis.…”
Section: The Literature Reviewmentioning
confidence: 99%
“…However, their research specifically focused on reducing energy consumption for cooling purposes. Banks et al [28] reported the results of their research on heat-pump water-heating systems. Of interest is the research conducted by Zhang et al [29], which compares the primary energy consumption, environmental impact, and heating costs of coal-fired and wall-fired gas boiler heating systems, direct electric heating systems, and air-source heat pump systems using a life cycle analysis.…”
Section: The Literature Reviewmentioning
confidence: 99%